An interoperability system for authentication and authorisation in VANETs. (22nd January 2010) - Casola, Valentina; Luna, Jesus; Mazzeo, Antonino; Medina, Manel; Rak, Massimiliano; Serna, Jetzabel
Vehicular ad hoc networks (VANETs) have evolved considerably over the last years, but despite the wide number of potential applications, VANETs also raise a broad range of critical security and privacy challenges. To achieve privacy, VANETs enforce the concepts of authentication and authorisation via public key infrastructures, relying on a large set of regional certification authorities with explicit cross-certification agreements to provide interoperability for vehicles and services. To avoid the burden of managing these cross-certificates, our research proposes the interoperability system (IS), an architecture to provide VANETs' nodes with a security mechanism for mutually untrusted domains. The IS supplies vehicles with a trusted set of credentials by implementing a certificate status service and a security level evaluator. This paper shows that the proposed architecture can be used to implement a mandatory access control mechanism in two VANET scenarios with a protocol independent of the underlying communication system.